2019
DOI: 10.3991/ijoe.v15i09.10671
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mobile Learning in the Cloud on Learning Competencies of Engineering Students

Abstract: <p class="0abstract">It has been acknowledged that the mobile learning concept has extended numerous opportunities for teachers as well as students, as it makes way for an active learning atmosphere anywhere and anytime.  Mobile learning technology can be resourcefully improvised by extending the cloud technology into it. This study is an attempt to analyze the impact of mobile cloud computing on learning competencies of engineering students. The main intention is to experiment whether mobile learning us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This first stage is carried out through student gadgets before learning in class. In addition to considerations of efficiency and effectiveness (Brown & Mbati, 2015;Crompton et al, 2016;Darmaji et al, 2019;Elmahdi et al, 2018;Mallya. K & Srinivasan, 2019), the use of gadgets, such as e-books connected with the Google Classroom application motivates students to prepare themselves before learning.…”
Section: / 20mentioning
confidence: 99%
See 2 more Smart Citations
“…This first stage is carried out through student gadgets before learning in class. In addition to considerations of efficiency and effectiveness (Brown & Mbati, 2015;Crompton et al, 2016;Darmaji et al, 2019;Elmahdi et al, 2018;Mallya. K & Srinivasan, 2019), the use of gadgets, such as e-books connected with the Google Classroom application motivates students to prepare themselves before learning.…”
Section: / 20mentioning
confidence: 99%
“…In other words, students are motivated to determine an insight on the solution to the problem. This second stage is also accommodated by the efficiency and effectiveness of students' gadgets (Brown & Mbati, 2015;Crompton et al, 2016;Darmaji et al, 2019;Elmahdi et al, 2018;Mallya. K & Srinivasan, 2019).…”
Section: / 20mentioning
confidence: 99%
See 1 more Smart Citation
“…The article [83] surveyed 40 undergraduate students for both traditional and mobile cloud modes of courses. It was identified that course outcomes for the mobile cloud mode were better than the traditional mode of learning.…”
Section: Csfs For Cloud-based Mobile Learningmentioning
confidence: 99%
“…At the same time, teachers can give timely feedback and guidance to students to help them correct their mistakes and improve their learning methods. Mallya [2] attempt to analyze the impact of mobile cloud computing on learning competencies of engineering students. The main intention is to experiment whether mobile learning using cloud technology has an impact on student's performance by investigating the influence of this innovative teaching technique on course outcomes.…”
Section: Introductionmentioning
confidence: 99%